Wheat Genetic Resources in Nepal - Joshi, BK; Mudwari, A; Bhatta, MR (Nepal Agriculture Research Journal, 2009)
Genetic diversity must be maintained and utilized for sustainable agriculture development. The amount of genetic diversity in the country depends on the number and diversity of the original ancestors involved in the creation of a germplasm pool, wild relatives and existing landraces. The objective of this research was to study the diversity of wheat gene pool present in the Nepalese bread wheat cultivars and landraces that could help for developing conservation and utilization strategy effectively. We examined the pedigrees of 35 Nepalese wheat cultivars and surveyed the literature for distribution of landraces and wild relatives of wheat. Cultivated landraces of spring and winter type, wild landraces and diploid species of wheat are found in Nepal. There are 35 improved wheat cultivars, 540 landraces and 10 wild relatives of wheat. Crosses between winter and spring wheat gene pools are far more common and offer a new source of diversity. Mexico, India and Nepal are the origin countries for 35 cultivars. In Nepal four cultivars were bred and developed using foreign landraces and maximum number of cultivars was developed in Mexico. Lerma 52, first improved cereal variety to be released in the history of cereal breeding in Nepal was released in 1960. A total of 89 ancestors originated in 22 different countries were used to develop these cultivars. Highest number of ancestors was from India. Ancestors of both aestivum and durum species having winter, spring and intermediate growth habit indicated the collection of wide gene pool. Most of the ancestors were aestivum (76.40%) and spring growth habit (57.31%). Modern varieties are replacing the landraces and improved old varieties resulted in the genetic erosion. Therefore, in situ, on farm and ex situ conservations are necessary for maintaining these genetic variations. Unutilization of local landraces in breeding program may be the major factor that causes to accelerate the genetic erosion. Gene pool from these landraces along with international gene pool could make towards success in developing high yielding cultivars with wide adaptability. In this study, cultivars and landraces surveyed represent a wide range of variation for different areas of origin and adaptation. Key words: Ancestor; landrace; origin; wheat gene pool DOI: 10.3126/narj.v7i0.1859 Nepal Agriculture Research Journal Vol.7 2006 pp.1-10